A survey of osteoderm histology and ornamentation among Crocodylomorpha: A new proxy to infer lifestyle?. (15th December 2022) - Pochat‐Cottilloux, Yohan; Martin, Jeremy E.; Amiot, Romain; Cubo, Jorge; de Buffrénil, Vivian
Abstract: Osteoderms of eight extant and extinct species of crocodylomorphs are studied histologically and morphologically. Most osteoderms display the typical "crocodilian" structure with a woven‐fibered matrix surrounded by an upper and a lower parallel fibered matrix. The dorsal ornamentation of those specimens consists of a pit‐and‐ridge structure, with corresponding remodeling mechanisms. However, an osteoderm of Iberosuchus, studied here for the first time, differs in being nearly devoid of ornamentation; moreover, it shows strong bundles of straight Sharpey's fibers perpendicular to the surface in its lateral and dorsal walls, along with a rough plywood‐like structure in its basal plate. This suggests that this osteoderm was more deeply anchored within the dermis than the other osteoderms studied hitherto. This peculiar structure might have been linked to a terrestrial ecology and a specific thermoregulation strategy. Some other notosuchians in our sample do not exhibit ornamentation on their osteoderms, as opposed to neosuchians. Considering current interpretations of osteoderm function(s) in crocodilians, our observations are discussed in reference to possible ecophysiological peculiarities of Notosuchia in general, and Iberosuchus in particular. Abstract : We present the first histological study of an osteoderm of Iberosuchus, comparing to other crocodylomorph taxa. It shows bundles of straight Sharpey's fibers, hinting at a more profound implantation in the dermis, linked with a terrestrial lifestyle and specific thermoregulation strategy. Osteoderm ornamentation might be linked to living environments.